Patient Aligned Care Team (PACT) Performance in Urban and Rural VHA Primary Care Clinics: A Mixed Methods Study. Issue 2 (6th July 2020) - Lampman, Michelle A.; Steffensmeier, Kenda R. Stewart; Reisinger, Heather Schacht; Sarrazin, Mary Vaughan; Steffen, Melissa J. A.; Solimeo, Samantha L.; Stewart, Greg L.; Mueller, Keith J.
Abstract: Purpose: To assess differences in Patient Aligned Care Team (PACT) performance between rural and urban primary care clinics within the Veterans Health Administration (VHA). Methods: An Explanatory Sequential Mixed Methods design was conducted using VHA administrative data to assess performance of a national sample of 891 VHA primary care clinics. Generalized Estimating Equations with repeated measures were used to estimate associations between rurality and process‐oriented endpoints including: chronic disease management through telehealth; use of telephone visits, group visits or secured messaging; same‐day access; continuity with primary care provider; and postdischarge follow‐up. Qualitative data collected during on‐site visits with 5 clinics were used to provide insights into PACT processes from the perspectives of staff in rural and urban clinics. Findings: After adjusting for patient‐ and practice‐level characteristics, clinics located in large rural or small/isolated rural areas demonstrated difficulty enhancing access through use of telephone visits, group visits, or secured messaging and completing postdischarge follow‐up calls, compared to urban clinics. Qualitative analysis indicated that staff from both rural and urban clinics reported similar barriers implementing these PACT processes. Both patient and staff behaviors and preferences impact implementation of these processes. Distance to care and access to high‐speed Internet were also reported as barriers. Conclusions: This study contributes to the understanding of PACT performance in rural settings by highlighting ways contextual and behavioral factors relate to performance. Increasing implementation of patient‐centered medical home (PCMH) models, such as PACT, will require additional attention to the complex relationships between the practice and surrounding context.